Urban mobility and the impacts caused by Covid-19: The paradox of public transport and the issue of social distance - Silva, Angela Tereza da; Oliveira , Weverton de; Ferreira, Evaldo (National Journal of City Management, 2021)
This pandemic portrayed the country's social and economic inequality in terms of health services, work and social distancing. It was found that the spread of Covid-19 on a global scale is favored by the circulation of infected people and/or objects; changing the circulation in many land and air borders that needed to have restricted and/or closed accesses, including, the reduction and even the suspension of travels inside and outside countries, whose displacements are by road, rail, river and sea. In view of this, the search for measures to face the pandemic within the various socio-economic contexts, such as in this case of urban mobility, for example, the occupancy limit of 50% of seats in intercity transport and the mandatory use of masks. Urban mobility permeates as a social right and essential service, which needs to continue to function with due health care. It is necessary to maintain social distance and take due care. For the country to remain in this confrontation, it is necessary to guarantee democratic access to the city, together with measures to protect social actors from contamination by the New Coronavirus.